Penggunaan Media Sosial Dan Media Massa Online Sebagai Public Sphere Di Era Milenial - Muhtar, Alvin Afif (Universitas Nahdlatul Ulama Blitar, 2024)
The concept of a public sphere, providing a space where everyone has the guarantee to gather, then expressing ideas or ideas without fear and pressure from any party In the current millennial era, Indonesians tend to involve themselves to contribute as citizens in issuing opinions or ideas via online . The formulation of the problem in this journal is: How is the use of social media and online mass media as a public sphere in the millennial era? Meanwhile, the objectives of this journal are: to determine the use of social media and online mass media as a public sphere in the millennial era. The results of the analysis in this journal show that the use of social media and online mass media as a public sphere in the millennial era is that both have the potential as a public sphere, namely providing free space that can be entered / accessed by many people, so that everyone can see and are free to express their opinions to respond to state problems. However, it has not been fully stated that it can be used as a public sphere because there are many phenomena that imprison any person who is trying to express his opinion through the online world on the basis of the assumption of defamation in the realm of law. Besides that, there is the nature of the media which tends to be full construction and not independent. The solution offered by the author is to provide a special public sphere via offline which can be used as a meeting between the government and the people and it is hoped that the government can create its own media that has a real independentnature.